2003
DOI: 10.2337/diacare.26.8.2426
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Insulin Sensitivity Check Index and the Reciprocal Index of Homeostasis Model Assessment in Normal Range Weight and Moderately Obese Type 2 Diabetic Patients

Abstract: OBJECTIVE -To investigate whether the quantitative insulin sensitivity check index (QUICKI) and the reciprocal index of homeostasis model assessment (1/HOMA-IR) derived from fasting plasma glucose and insulin level are excellent surrogate indices of insulin resistance in both normal range-weight and moderately obese type 2 diabetic and healthy subjects. RESEARCH DESIGN AND METHODS -The association between QUICKI or 1/HOMA-IR and insulin resistance index assessed by euglycemic-hyperinsulinemic clamp (clamp-IR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(127 citation statements)
references
References 32 publications
5
116
1
4
Order By: Relevance
“…Also, a statistically significant negative correlation was noted between testis weight and the HOMA index in diabetic rats. The HOMA index is generally used as an indicator of insulin resistance in both human and rodents [15,16,24]. Our studies suggest that hyperglycemia or insulin resistance may primarily induce testis atrophy, subsequently causing a reduction in spermatogenesis, which was more remarkably observed in diabetic rats than in non-diabetic rats.…”
Section: Discussionmentioning
confidence: 61%
“…Also, a statistically significant negative correlation was noted between testis weight and the HOMA index in diabetic rats. The HOMA index is generally used as an indicator of insulin resistance in both human and rodents [15,16,24]. Our studies suggest that hyperglycemia or insulin resistance may primarily induce testis atrophy, subsequently causing a reduction in spermatogenesis, which was more remarkably observed in diabetic rats than in non-diabetic rats.…”
Section: Discussionmentioning
confidence: 61%
“…First, more strict criteria for defining rosiglitazone-responder could not be adopted because of short planned duration of rosiglitazone treatment. Second, although it has been shown that both HOMA IR and QUICKI provide strong correlations with insulin resistance index assessed by euglycemic-hyperinsulinemic clamp [28,29], these parameters must be interpreted with caution because of the wide degree of variability compared with euglycemic-hyperinsulinemic clamp, the gold standard method for assessing insulin resistance and of a limited value of HOMA IR and QUICKI for elderly patients with poorly controlled T2DM [30]. Lastly, as few studies have been conducted in the Asian populations with regard to racial differences in body composition, regional fat distribution, and insulin resistance [31][32][33][34][35][36], more results on the change of body composition or fat redistribution and the comparison of regional fat distribution between the responder and nonresponder might be useful to verify the TZDs effect on body fat and to predict and classify rosiglitazone-responders by fat distribution when applicating TZD in non-obese or obese Asian diabetic patients.…”
Section: Discussionmentioning
confidence: 97%
“…The homeostasis model assessment of insulin resistance (HOMA-IR): fasting glucose (mg dl À1 ) Â fasting insulin (mU ml À1 )/405. 25 Plasma NE, insulin and leptin were measured as previously reported. 23 …”
Section: Measurementsmentioning
confidence: 99%